2013
DOI: 10.1103/physrevb.87.024408
|View full text |Cite
|
Sign up to set email alerts
|

Broadband diamagnetism in anisotropic metamaterials

Abstract: We discuss the strategy for achieving the values of the effective magnetic permeability much smaller than unity by employing an appropriate arrangement of metamaterial elements ("meta-atoms"). We demonstrate that strong diamagnetism over a very wide frequency range can be realized in metamaterials by employing nonresonant elements with deeply subwavelength dimensions. We analyze the effect of the lattice parameters on the diamagnetic response and find that selecting an appropriate lattice type is crucial for o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
21
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 21 publications
(22 citation statements)
references
References 16 publications
1
21
0
Order By: Relevance
“…Recently, this problem has been revisited by Lapine et al [6] and also by Belov et al [7]. In the first case [6], it was shown that a dense hexagonal lattice of closed loops with realistic parameters can deliver effective bulk permeability as low as 0.05. However, this design is necessarily anisotropic, which may pose an obstacle for certain applications.…”
Section: Introductionmentioning
confidence: 99%
See 4 more Smart Citations
“…Recently, this problem has been revisited by Lapine et al [6] and also by Belov et al [7]. In the first case [6], it was shown that a dense hexagonal lattice of closed loops with realistic parameters can deliver effective bulk permeability as low as 0.05. However, this design is necessarily anisotropic, which may pose an obstacle for certain applications.…”
Section: Introductionmentioning
confidence: 99%
“…1(a), with those for a sphere made of an artificial diamagnetic metamaterial-an anisotropic lattice of closed conducting loops [6]. We consider rings of mean radius r 0 , made of a metallic wire (with the same conductivity σ ) of circular cross section with radius r w .…”
Section: B a Sphere Of An Artificial Medium Made Of Conducting Loopsmentioning
confidence: 99%
See 3 more Smart Citations